CLASSIFICATION AND GROWTH OF VEGETATION UNITS IN MIXED RAINY FOREST, SÃO FRANCISCO DE PAULA, RS - Juliana Fernandes Gomes; Solon Jonas Longhi; Maristela Machado Araújo; Doádi Antônio Brena (Ciência Florestal, 2009)
This work was developed with the objective of studying the present ecological groups in the Mixed Rainy Forest and of describing the composition and the growth dynamics during the four seasons. The work had been accomplished in ten permanent conglomerates of 1 ha (100m x 100m), which were divided into ten strips of 10m x 100m (1000m2) and these ones subdivided into ten subunits of 10m x 10m (100m2). In this research, one 10m x 100m strip in conglomerate was selected, totaling ten subunits, where it had been installed, at BHD height, dendrometric bands in all trees with CBH ≥ 30 cm, to verify the annual and the seasonal growth. The density per species formed a matrix (99 x 39) used to test vegetation grouping through TWINSPAN (Two-way indicator species analysis), since three ecological groups were verified. Group 1 was denominated primary forest; group 2, humid site forests, and group 3, secondary forest. ≥ 30 cm. The annual average increment was larger for the primary forest, following the secondary forest and the forest of humid places. In decreasing order, the average periodic increment was larger in the summer, spring, autumn and winter. The species that stood out in density terms and increment were Cupania vernalis and Nectandra megapotamica.